MODEL TARIKAN PERGERAKAN TRANSPORTASI PADA KOMPLEKS LIPPO PLAZA, FLOBAMORA MALL DAN HYPERMART BUNDARAN PU KOTA KUPANG - Frans, John H.; Utomo, Sudiyo; Normandiri, Annisa E. (Jurnal Teknik Sipil, 2016)
Shopping center as one of land use, have a high enough intensity to attract people. The big attraction depends on many variables that influence it. Therefore this study aims to model the trip attraction and accumulation model vehicles parking on three shopping center in Kupang City are Lippo Plaza, Flobamora Mall and Hypermart Bundaran PU. Modelling done by using multiple linear regression analysis and multinomial logistic regression analysis. The result of the analysis in this study is obtained by modelling Y1 = 715,522 + 5,963 X3 + 0,056 X5, Y2 = 417,134 + 2,350 X3 + 0,020 X6, Y3 = 66,357 + 0,792 X3 + 0,023 X5and Y4 = 28,147 + 0,296 X3 + 0,006 X6, with Y1 is trip attraction two wheeled vehicles, Y2 is trip attraction four wheeled vehicles, Y3 is the accumulation of two wheeler parking, Y4 is the accumulation of four wheeler parking, the X3 is the number of tenants, X5 is a parking area for motorcycles and X6 is a four wheel vehicle parking area.Factors that influence the occurrence of trip attraction is earning the visitors a shopping center and factors elections comparison shopping center is a range of product, product quality, product availability, product pricing and parking facilities located at the shopping center.